Use of medicinal plants as a remedy against lymphatic filariasis: Current status and future prospect - Fatima A. Fordjour; Priscilla Osei‐Poku; Afua K. A. Genfi; Kwaw G. Ainooson; Kingsley Amponsah; Patrick K. Arthur; G. Richard Stephenson; Alexander Kwarteng (Health Science Reports, 2023)
Abstract Despite the successes achieved so far with the Global Programme to Eliminate Lymphatic Filariasis, there is still an appreciable number of lymphatic filarial patients who need alternative treatment and morbidity management strategies. The unresponsiveness of some cohorts to the drugs used in the mass drug administration program is currently raising a lot of questions and this needs urgent attention. Natural medicinal plants have a long‐standing history of being effective against most disease conditions. Countries such as India have been able to integrate their natural plant remedies into the treatment of lymphatic filarial conditions, and the results are overwhelmingly positive. Components of Azadirachta indica A. Juss, Parkia biglobosa, Adansonia digitata, and Ocimum spp have been shown to have anti‐inflammatory, anticancerous, and antimicrobial activities in animal models. Therefore, this review calls for attention toward the use of natural plant components as an alternate treatment against lymphatic filariasis to help reduce the World Health Organization's burden of providing drugs for people in need of treatment every year.